Olfactory dysfunction and coronavirus disease 2019 severity: a prospective cohort study. Issue 11 (9th November 2021) - Aydemir, L; Sen, C; Kara, H; Demir, A A; Bozbora, E; Uysal, E; Kesimli, C; Orhan, K S; Comoglu, S; Keles Turel, M N
Abstract: Objective: The primary goal of this study was to evaluate the association between olfactory dysfunction or taste impairment and disease severity and radiological findings in coronavirus disease-2019. The secondary goal was to assess the prevalence, severity and course of olfactory dysfunction or taste impairment in patients with coronavirus disease 2019. Method: This prospective observational cohort study evaluated patients hospitalised with coronavirus disease 2019 between April 1 and 1 May 2020. Olfactory dysfunction and taste impairment were evaluated by two questionnaires. Chest computed tomography findings and coronavirus disease-2019 severity were assessed. Results: Among 133 patients, 23.3 per cent and 30.8 per cent experienced olfactory dysfunction and taste impairment, respectively, and 17.2 per cent experienced both. The mean age was 56.03 years, and 64.7 per cent were male and 35.3 per cent were female. No statistically significant association was found between olfactory dysfunction ( p = 0.706) and taste impairment ( p = 0.35) with either disease severity or chest computed tomography grading. Conclusion: Olfactory dysfunction or taste impairment does not have prognostic importance in patients with coronavirus disease 2019.